2012
DOI: 10.1002/j.1556-6676.2012.00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Description of an Intensive Dialectical Behavior Therapy Program for Multidiagnostic Clients With Eating Disorders

Abstract: The authors describe an intensive outpatient dialectical behavior therapy (DBT) program for multidiagnostic clients with eating disorders who had not responded adequately to standard, empirically supported treatments for eating disorders. The program integrates DBT with empirically supported cognitive behavior therapy approaches that are well established for the treatment of eating disorders. Attention is given to inclusion and exclusion criteria, how the program differs from standard treatments for eating dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Use of DBT techniques. The clinicians provided details of their use of a range of DBT techniques when treating eating disorders, taken from a DBT manual for eating disorders (Federici et al, 2012;Safer et al, 2009). These are detailed in Table 1 and in the Results.…”
Section: Measures and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of DBT techniques. The clinicians provided details of their use of a range of DBT techniques when treating eating disorders, taken from a DBT manual for eating disorders (Federici et al, 2012;Safer et al, 2009). These are detailed in Table 1 and in the Results.…”
Section: Measures and Proceduresmentioning
confidence: 99%
“…It is also unclear whether DBT clinicians working with eating disorders form a homogeneous group (all delivering techniques in a similar pattern), or whether they fall into heterogeneous groups (each group delivering a distinct pattern of techniques). Although it is clear that CBT and FBT clinicians each fall into such groups when working with eating disorders (Kosmerly et al, 2015;Waller et al, 2012), it is possible that this finding will not apply to self-identified DBT practitioners in the field of eating disorders (Federici, Wisniewski, & Ben-Porath, 2012;Safer, Telch, & Chen, 2009). Therefore, the primary aim of the present study was to determine the extent to which core DBT techniques are used by DBT clinicians treating patients with eating disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, researchers have included aspects such as phone coaching or skills groups in addition to traditional treatment approaches for optimal treatment outcomes (Ben-Porath, Federici, Wisniewski, & Warren, 2014). In other situations, especially for adolescents who are the most difficult to treat, clinicians implemented full DBT concurrently with another full treatment approach (Bhatnagar & Wisniewski, 2015;Federici, Wisniewski, & Ben-Porath, 2012). Similarly, counselors could consider implementing DBT only after evidenced-based treatments have proved unsuccessful.…”
Section: Implications For Practicementioning
confidence: 99%
“…While the above‐mentioned studies have primarily investigated the viability of DBT as a stand‐alone treatment approach for eating disorders, the integration of DBT treatment with evidence‐based treatment approaches for eating disorders has also been proposed as potentially beneficial in adult and adolescent populations, especially for those patients with a history of chronic treatment failure and severe life‐threatening and therapy‐interfering behaviors (Federici, Wisniewski, & Ben‐Porath, ; Federici & Wisniewski, ). For adolescents, Federici and Wisniewski () suggest that DBT and FBT can be integrated on an outpatient basis and describe the ways in which DBT is theoretically compatible with FBT.…”
Section: The Maudsley Approachmentioning
confidence: 99%